Survival Strategies in the Digital Age: A Case Study of Vivigkt Store A Contemporary Fashion Store in Tegal - Risqiyanti, Mufatikhatun (Jeksyah: Islamic Economics Journal, 2025)
Digital transformation has significantly impacted the micro, small, and medium enterprise (MSME) sector, particularly in the fashion industry where rapid trend shifts and consumer demands require adaptive and innovative strategies. This study explores the survival strategies of Vivigkt Store, a local fashion retailer in Tegal Regency, in responding to digitalization challenges. Using a descriptive qualitative approach with in-depth interviews, the research examines how the store manages digital marketing, builds customer relationships, and maintains brand consistency across online and offline platforms. The findings indicate that Vivigkt Store adopts content marketing optimization, ensures seamless customer experiences, and delivers consistent service quality, reflecting the principles of the Dynamic Capabilities Theory. The study’s practical contribution is offering insights for local MSMEs on adopting scalable, cost-effective digital strategies focused on customer experience. Its novelty lies in presenting a case study of a rural MSME that successfully integrates digital tools and omnichannel approaches, an area rarely addressed in current literature.